(NoPYTY NEWEVDY (B/s - (NmONTENX(B, (NmI[ELX |JKEM DEs 1533-1592 ((NsANKT(B-(NpETERBURG (B:s (NiZDATELXSKIJ DOM (B"(NnEWA(B",s, 2005)
(NiZDANIE SODERVIT(B: (NO bOGE(B; (NO VIZNI(B; (NO SMERTI(B; (NO DRUVBE(B; (NO SEBE(B.s
Keywords: (NfRANCUZSKAQ LITERATURA (B- (NKON(B. 15-16 (NWW(B. ((N\POHA wOZROVDENIQ(B) - (NfILOSOFSKO(B-(N\STETI^ESKIE O^ERKIs; (NfILOSOFIQ fRANCII (B- (NfRANCUZSKOE wOZROVDENIE (B(XV-XVI (NWW(B.) - (NsKEPTICIZMs